Identification of a novel SPTB gene splicing mutation in hereditary spherocytosis: a case report and diagnostic insights - Li, Xiaobing; Zhang, Tingqiang; Li, Xuemei; Wang, Li; Li, Qian; Liu, Qianqian; He, Chengyin; Zhang, Li; Liu, Yongsheng; Tang, Junling (Frontiers in Genetics, 2025)
BackgroundHereditary spherocytosis (HS) is a group of genetically heterogeneous hereditary hemolytic disorders characterized by anemia, splenomegaly, jaundice, reticulocytosis, and spherical red blood cells on peripheral blood smears. Mutations in key genes, including SPTB, ANK1, SLC4A1, SPTA1, and EPB42, are commonly implicated in HS.Case PresentationWe report the case of a 22-year-old female presenting with anemia, jaundice, and a family history of splenectomy. Laboratory investigations revealed hemolytic anemia, elevated bilirubin levels, and peripheral blood smear findings consistent with HS. Genetic testing identified a novel SPTB gene splicing mutation (NM_001355436.2: c.1645-1G>A), inherited maternally, which is predicted to disrupt normal RNA splicing and protein synthesis.DiscussionThe identified SPTB mutation expands the known mutation spectrum of the SPTB gene and highlights its role in the pathogenesis of HS. Clinical findings, combined with genetic analysis, confirmed the diagnosis of HS and underscored the importance of comprehensive molecular testing for accurate diagnosis, especially in patients with a strong family history.ConclusionThis case emphasizes the utility of genetic testing in diagnosing hereditary spherocytosis, particularly for novel gene mutations. Early and accurate molecular diagnosis facilitates better clinical management, family counseling, and treatment decisions for patients with HS.